ANALISIS PENDAPATAN PETANI PADI SAWAH DI KELURAHAN IKUA KOTO DIBALAI KECAMATAN PAYAKUMBUH UTARA KOTA PAYAKUMBUH - Jaka Septian Cahyadi; Sri Mariya (JURNAL BUANA, 2022)
AbstractThis study aims to determine the needs of rice farmers, the factors that influence the success of rice farmers' businesses, and the obstacles experienced by farmers in rice farming in Ikua Koto Village, Dibalai, North Payakumbuh District. This type of research is descriptive qualitative using primary data as a source of data obtained through interviews. The informants in this study were rice farmers in the Ikua Koto Village in the Balai. The data were analyzed using data reduction and display. The results of this study found that the needs in rice farming include plow machines, seeds, sufficient capital, fertilizers, pesticides, and irrigation water. Success in rice farming includes adequate irrigation, sufficient fertilizer, maximum care from rats, birds, and snails, sufficient capital and labor such as assistance from other people in rice farming. Constraints in rice farming include irrigation water, especially in the dry season, water is very difficult, fertilizers are difficult to obtain and the amount of capital is small.